CLINICAL AND DIAGNOSTIC ON RINGWORM INFECTION IN CATTLE IN DIYALA PROVINCE OF IRAQ - A. M. , Khalaf; K. A. , Al-Salehi (The Iraqi Journal of Veterinary Medicine, 1996)
Dermatomycosis (ringworm) was studied in 15 infected, out of 55 examined cows, 6 months to 2 years of age. Infected cows showed typical clinical signs and lesions of ringworm. Both types of dermatophytes i. e. Trichophton and microsporum were isolated from these cases. The isolates were the following: Tr. Verrucosum (40%), Tr. mentagrophytes (6.6%), Tr. megnini (6.6%), Tr. ajelloi (20%), M. nanum (20%) and M. gypseum (6.6%).